Histopathological Analysis of Metastatic Tumours of the Oral Cavity with Example of Metastatic Renal Cell Carcinoma to Tongue - Vučković Ljiljana; Miladinović Mirjana; Popović Vladimir; Janjić Nevenka Lukovac; Borilović Milena; Đuričković Mirjana (Balkan Stomatological Society, 2020)
Background/Aim: Metastatic tumours make up only 1-3% of all malignant tumours of the oral region; however, in 25% of the total number of cases, they are the first sign of the disease. Usually, metastases in the oral region are followed by poor prognosis. Metastases are more common in the mandible than in the maxilla; in soft tissues, they most commonly occur in the attached gingiva and tongue. Malignant tumours of the lung, breast, kidney, liver, bone, prostate, thyroid gland, skin, colon and female genital organs most commonly give metastases in this region, usually in patients aged 40 to 70 years.